Framework and Development of a Collaborative Supply Chain Model - Ben-faress, Mouad; Elouadi, Abdelmajid; Gretete, Driss (International Journal of Supply Chain Management, 2019)
One of the most critical issues of inventory management is Customer demand (intermittent demand, request for change in product, process or phase in / out). Variation in demand increases the difficulty of determining the precise amount of inventory both to avoid stockout and to satisfy the customer fill rate. The inventory control problem is getting complicated by the fact that demand is uncertain or the variation of demand is highly volatile. [1]. Many practical systems such as manufacturing and inventory systems applications are mostly used to model categorical data sequences. [2]. Results indicate that firms that focus on flexibility, quality, and delivery should develop strategic collaboration with suppliers & customers to achieve market and innovation improvement. Cost- and quality-focused firms should develop operational collaboration to achieve resource efficiency. The model allows understanding the right alignment of external suppliers and customers being pursued to for key performance development and continuous improvement insight.